The virtual flow cytometer: A new learning experience and environment for undergraduate teaching - Francis, Nigel J.; Ruckley, Dave; Wilkinson, Thomas S. (Frontiers in Education, 2022)
Background The use of simulations has been steadily rising in popularity in the biosciences, not only due to the COVID-19 pandemic restricting access to physical labs and equipment but also in the face of rising student numbers. In this study, we describe the development and implementation of a novel, open-access interactive simulation used to not only supplement a laboratory class but to enhance the student learning experience. The simulation provides students with the opportunity to interact with a virtual flow cytometer, design a simple experiment and then critically analyse and interpret raw experimental data. Results Results showed that this highly authentic assessment used a much broader range of the mark scheme acting as an excellent discriminatory for student ability compared to simple recall as assessed by multiple choice questions. Overall, the student response to the new assessment was positive, highlighting the novelty of the assessment, however, some students did experience technical issues when the simulation was used for the first time. Conclusions Simulations can play a crucial role in the student learning cycle by providing a rich, engaging learning environment, however, they need to be used to supplement other hands-on experiences to ensure that students acquire the necessary kinematic skills expected of a successful science graduate.